Assessing Health Worker Opinions on Hybrid Professionalism in Clinical Directorates: Including Clinicians in Management - ALSHABI, YOSRA AHMED; Masoud, Wadyan Fisal; Masoud, Khalid Faisal Mohammed; Alqurashi , Faisal Menwer; Aljohani, Adnan Mohammed Rajab; ahmed, Afaf ddh mohamed; Alsagoor, Alhussain Saleh Mohammed; Albarqi , Nahla Mufareh Mohammed; alghanim, Ibrahim mohammed ibrahim; Alharbi , Dareen Mohammed Ali (Journal of Ecohumanism, 2024)
Background: The introduction of managerial reforms in healthcare has disrupted traditional professional values, including autonomy and patient-centered care. A model of "hybrid" professionalism, where healthcare workers assume managerial roles, has been proposed to bridge the gap between clinical practice and management. This model aims to enhance collaboration, efficiency, and clinical governance while reducing tensions between distinct professional values. Despite its potential benefits, the implementation of hybrid professionalism in healthcare settings has been met with challenges. This study explores healthcare workers’ perceptions of hybrid professionalism within clinical directorates (CDs), focusing on the attitudes of those in managerial roles. Methods: This study was conducted within a large urban healthcare system with approximately 8,000 healthcare professionals. A 65-item questionnaire, including Likert-scale and open-ended questions, was distributed to healthcare workers in managerial roles, including unit managers and department heads. The survey focused on leadership roles, interprofessional collaboration, decision-making, and the impact of managerial responsibilities on clinical practice. A total of 123 healthcare professionals participated in the study, with responses analyzed using both quantitative and qualitative methods. Results: Quantitative results revealed that 65% of unit managers and 60% of supervisors agreed on the effectiveness of hybrid roles in leadership, with 70% of both groups emphasizing the importance of teamwork between clinical and managerial staff. However, some uncertainty was expressed regarding the long-term sustainability of hybrid roles, particularly in balancing clinical and managerial tasks. The qualitative analysis identified key themes such as the challenges of balancing clinical expertise with managerial responsibilities, the importance of collaboration, and the benefits and complexities of hybrid roles. Conclusion: Hybrid professionalism in healthcare, particularly within clinical directorates, is seen as beneficial for organizational governance and collaboration. However, there are concerns about the sustainability and workload associated with hybrid roles. The findings suggest that hybrid managers need strong leadership skills and that team-based approaches, particularly with the support of nursing managers, are essential for the successful integration of clinical and managerial responsibilities. Future studies should explore the impact of hybrid roles in other healthcare contexts and organizational structures.